2022
DOI: 10.1136/bmjdrc-2022-002867
|View full text |Cite
|
Sign up to set email alerts
|

Level of education is associated with coronary heart disease and chronic kidney disease in individuals with type 2 diabetes: a population-based study

Abstract: IntroductionTo study the relationship between education level and vascular complications in individuals with type 2 diabetes in Norway.Research design and methodsMultiregional population-based cross-sectional study of individuals with type 2 diabetes in primary care. Data were extracted from electronic medical records in the period 2012–2014. Information on education level was obtained from Statistics Norway. Using multivariable multilevel regression analyses on imputed data we analyzed the association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Level of education is another factor associated with poorer glycemic control and a higher risk of complications [3,[27][28][29]. The present study showed that having a tertiary education was associated with maintaining a normal glycated hemoglobin result below 7% in subjects with type 1 diabetes.…”
Section: Discussionsupporting
confidence: 49%
“…Level of education is another factor associated with poorer glycemic control and a higher risk of complications [3,[27][28][29]. The present study showed that having a tertiary education was associated with maintaining a normal glycated hemoglobin result below 7% in subjects with type 1 diabetes.…”
Section: Discussionsupporting
confidence: 49%
“…In the present study, two demographic variables, marital status and education level, were identified as parameters that can predict the risk of 5-year all-cause mortality, indicating that social support may play an important role in the clinical outcomes of both diabetes and hypertension. In a population-based study, Slåtsve et al [ 19 ]. demonstrated that higher education levels were associated with lower odds for coronary heart disease and chronic kidney disease in individuals with type 2 diabetes, and higher education was also found to affect their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest significant progress in CVD management and prevention strategies over the past two decades, possibly driven by advancements in medical care, improved access to healthcare services, and greater emphasis on preventive measures. Continued efforts to monitor and address cardiovascular risk factors among individuals with diabetes are essential to sustain these positive trends and further reduce the incidence of cardiovascular complications in this high-risk population [24][25][26].…”
Section: Discussionmentioning
confidence: 99%